IMPLEMENTASI TEKNIK TRIPLE P DALAM MEMUDAHKAN GURU BAHASA INGGRIS SMA N 4, SMA N 5, DAN SMA N 8 KOTA JAMBI MENULIS PROPOSAL PENELITIAN TINDAKAN KELAS - Nurmaini MY (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
This school action research is aimed at increasing English teachers ability to write classroom action research proposal through the use Triple P technique ( Presentation, Practice and Produce ). The subjects of this research are English teachers at SMA N 4, SMA N 5 and SMA N 8 Kota Jambi. Data  was collected through interview, document, observation and instrument of test. This research consists of two cycles. The result of cycle 1 states  the average score of English teachers at SMA N 4 is 58.75, SMA N 5 is 65 and teaches at SMA N 8 is 50.. It increases 41.25% comparing to  the initial score 17.5,. The average score of English teachers increases 40% comparing to initial average score 25. The result of cycle 2 states English teachers at SMA N 4 get 75, SMA N 5 get 84.5 and teaches at SMA N 8 get 80.5. It increases 16.25% for SMA N 4, 19.5 for SMA N 5 and 30.5% for SMA N 8.The grand mean of  the subject under study in writing CAR proposal is 79.61. There is 17..32 % comparing to the result of in cycle 1.  Based on this result can be concluded that triple P technique is significant enough to make  English teachers of SMA N 4, SMA N 5, and SMA N 8 Kota Jambi  write CAR Proposal easily.Keywords: Presentation, Practice, Production, Research